2013
DOI: 10.1080/09712119.2013.792732
|View full text |Cite
|
Sign up to set email alerts
|

The effect of probiotic supplementation on the growth performance, blood biochemistry and immune response of reciprocal F1 crossbred (Rhode Island Red×Fayoumi) cockerels

Abstract: A study was conducted to evaluate three different probiotic levels, using drinking water supplemented with 0 (control), 1, 2 or 3 ml/L of Protexin (probiotic). In a 2 )4 factorial design, 360 of each reciprocal crossbred (Rhode Island Red [RIR] )Fayoumi [FY]) cockerels (six weeks old) were randomly assigned to four dietary treatments. Each diet was offered to three pens of 30 RIR )FY cockerels each or three pens of 30 FY )RIR cockerels each. At 12 weeks of age, body weight (BW) and feed conversion were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 41 publications
3
9
0
Order By: Relevance
“…The present research findings are in agreement with a previous study which reported less FI in probiotic-treated cockerel crossbreds [ 15 ], but differ from other reports [ 3 , 11 , 14 , 26 ], who have stated a higher significant FI ( p < 0.05) in probiotic-fed broilers than that of the antibiotic and control groups. However, no influence of various probiotics on the FI of birds was reported in previous studies [ 25 , 27 – 30 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The present research findings are in agreement with a previous study which reported less FI in probiotic-treated cockerel crossbreds [ 15 ], but differ from other reports [ 3 , 11 , 14 , 26 ], who have stated a higher significant FI ( p < 0.05) in probiotic-fed broilers than that of the antibiotic and control groups. However, no influence of various probiotics on the FI of birds was reported in previous studies [ 25 , 27 – 30 ].…”
Section: Discussionsupporting
confidence: 88%
“…However, they found a similar ADG like the current study. Although a similar BWG and ADG has been reported in egg-type male growing chicken, no significant differences were reported between basal and low probiotics (1 gm/l) fed to crossbreds of Fayoumi and Rhode Island Red cockerels [ 15 , 16 ]. Despite the few studies, the majority of the results stated that probiotics have a greater effect on BWG of the birds than that of antibiotic growth promoters [ 2 , 3 , 11 , 17 25 ].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Differences between physical and environmental conditions of the trials may also bias the results from these studies (Olnood et al, 2015). Also, an accurate dosage of administration has not yet to be established despite the wide use of probiotics (Khan et al 2013;Li et al, 2014;Abu-Akkada andAwad, 2015 andGetachew, 2016). A continuously giving the probiotics via drinking water to the broiler chicken at whole breeding period may be more trusted way for taking maximum profit from it.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in blood composition were not observed in all the cases of probiotic use in birds. When feeding birds with bacteria of genus Lactobacillus, Bifidobacterium, Pediococcus, there were no significant changes in blood composition (Khan et al, 2013;Al-Saad et al, 2014).…”
Section: Discussionmentioning
confidence: 94%